2008
DOI: 10.1002/rcs.184
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional ultrasound‐guided robotic needle placement: an experimental evaluation

Abstract: Background Clinical use of image-guided needle placement robots has lagged behind laboratory-demonstrated robotic capability. Bridging this gap requires reliable and easy-to-use robotic systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(104 citation statements)
references
References 36 publications
2
101
0
1
Order By: Relevance
“…Needle placement covers applications like biopsies, fluid extraction from internal organs (cardiac tamponade, lungs) or placement of radioactive seeds in different body organs in minimally invasive cancer therapy [1][2][3]. In [1] it is shown that a robotic device enhances the needle placement precision beyond the natural human capabilities.…”
Section: "A Wise Man Should Consider That Health Is the Greatest Of Hmentioning
confidence: 99%
See 1 more Smart Citation
“…Needle placement covers applications like biopsies, fluid extraction from internal organs (cardiac tamponade, lungs) or placement of radioactive seeds in different body organs in minimally invasive cancer therapy [1][2][3]. In [1] it is shown that a robotic device enhances the needle placement precision beyond the natural human capabilities.…”
Section: "A Wise Man Should Consider That Health Is the Greatest Of Hmentioning
confidence: 99%
“…These techniques provide a set of images enabling the preplanning of the procedure where the physician defines safe linear trajectories to reach the targeted point(s). Nevertheless, in order to increase the safety of the procedure it is desired to have a real-time visual feedback of the needle placement during the procedure to reduce the risk of damaging any internal body structures [2]. During the first steps of introducing robotic systems in medical arena, the imagistic methods that can be used during the needle placement were defined [3,4]: High Intensity Focal Ultrasound (HIFU), CT, MRI and Positron Emitted Tomography (PET Scan).…”
Section: "A Wise Man Should Consider That Health Is the Greatest Of Hmentioning
confidence: 99%
“…Most of the work in this category has focused on tracking needles, catheters or surgical grippers in 2D ultrasound images [25], and recently on tracking the shaft of instruments [10], [12], [6], [8] using 3D ultrasound.…”
Section: Related Workmentioning
confidence: 99%
“…(6) (7) (8) Here, estimated parameters are labeled by , | · | takes the absolute value, and || · || represents the norm of a vector.…”
Section: Simulationmentioning
confidence: 99%
See 1 more Smart Citation